Longitudinal Association of Poor Sleep Quality With Chemotherapy-Induced Nausea and Vomiting in Patients With Breast Cancer. Issue 8 (October 2016) - Jung, Dooyoung; Lee, Kwang-Min; Kim, Won-Hyoung; Lee, Joo-Young; Kim, Tae-Yong; Im, Seock-Ah; Lee, Kyung-Hun; Spiegel, David; Hahm, Bong-Jin
ABSTRACT: Objective: Risk factors for chemotherapy-induced nausea and vomiting (CINV) include older age, female sex, alcohol consumption, and a history of motion sickness. Although gastrointestinal symptoms are found to be related with sleep and mood in other conditions, little is known about their effects on CINV. Methods: This prospective observational study recruited patients with early-stage breast cancer who had recovered from surgery before receiving a first cycle of anthracycline and cyclophosphamide–based chemotherapy. Candidate factors associated with CINV were assessed before chemotherapy by using the following: the Pittsburgh Sleep Quality Index, the Insomnia Severity Index, the Epworth Sleepiness Scale, and the Hospital Anxiety and Depression Scale. Chemotherapy-induced nausea (CIN) and chemotherapy-induced vomiting (CIV) were defined according to a numeric rating scale (0–10) as follows: ≥3, nausea; ≥1, vomiting. Results: Between February 2012 and May 2014, data were collected from 198 patients. Chemotherapy-induced nausea occurred in 35.4% of patients, and CIV occurred in 31.3%. Chemotherapy-induced nausea was significantly associated with poor sleep quality (odds ratio [OR], 2.48; 95% confidence interval [CI], 1.13–5.46; p = 0.024) and pretreatment nausea (OR, 4.81; 95% CI, 1.84–12.62; p = 0.001). Likewise, CIV was significantly associated with poor sleep quality (OR, 2.64; 95% CI, 1.21–5.78; p = 0.015) and pretreatment nausea (OR, 3.07; 95% CI, 1.23–7.66; p = 0.016). Conclusions: Poor sleep quality increases risk of CINV in patients with breast cancer. Sleep problems should be assessed and considered in the management of CINV. Abstract : Supplemental digital content is available in the text.